Fenomena Sex in the Car di Aceh dalam Perspektif Fiqh Jinayah dan Maqashid Syariah - Retanisa Rizqi (TAQNIN: Jurnal Syariah dan Hukum, 2025)
This study examines the phenomenon of sex in the car in Aceh within the framework of fiqh jinayah (Islamic criminal law) and maqasid al-syari‘ah (the objectives of Islamic law) to explore its legal, moral, and policy implications in the enforcement of Islamic law. The research focuses on how sexual activity inside a vehicle is classified within the categories of jarimah (hudud/ta‘zir) and the extent to which such acts violate the five essential objectives of Islamic law (al-dharūriyyat al-khams). The study employs a normative legal research method, analyzing statutory regulations (Qanun Aceh No. 6/2014), classical and contemporary fiqh literature, and the maqasid framework as a conceptual basis. Secondary data were obtained from books, journals, and official reports published within the last six years. The findings reveal that the sex in the car phenomenon is generally categorized as a jarimah ta‘zir, which requires discretionary punishment by the authorities, while simultaneously violating the core elements of maqasid (particularly hifẓ al-din, hifẓ al-nafs, and hifẓ al-nasl). The study further emphasizes the need to recontextualize fiqh jinayah to address contemporary forms of khalwat, such as in vehicles, through preventive legal measures (sadd al-dzari‘ah), clear evidentiary guidelines, and the integration of educational approaches. The novelty of this research lies in its empirical focus on vehicles as modern spaces of khalwat in Aceh and its maqasid-based normative recommendations for adaptive Islamic law enforcement.